Pendampingan Legalitas dan Identitas UMKM melalui Pembuatan NIB, dan Label Produk, Berbasis ABCD di Desa Bungatan Situbondo (Lembaga Pengembangan Kinerja Dosen, 2025)
The village of Bungatan in Situbondo Regency, East Java, has significant economic potential through the presence of micro, small, and medium enterprises (MSMEs) spread across various sectors. However, the main issues faced by the MSME community in Bungatan Village include low legal literacy regarding business licensing, weak product identity in terms of design and information, and limited use of effective promotional media. Based on this, the objective of this community service activity is to increase the number of MSMEs with business legality, strengthen product identity to enhance competitiveness in the market, and build relevant visual promotion capabilities aligned with local characteristics. The method employed is the Asset-Based Community Development (ABCD) approach. The ABCD approach aims to raise community awareness of the assets they possess. The results of the SME development program in Bungatan Village demonstrate significant improvements in business legality, product identity, and promotional capacity through the Asset-Based Community Development (ABCD) approach. Overall, the outcomes of this activity indicate that empowerment based on local potential and active community participation can strengthen community economic resilience and open opportunities for sustainable SME development.